The Boy in the Oven: The Arabic Infancy Gospel and an Anti-Jewish Tale in Medieval Iberia - Giles, Ryan D. (2022)
This study examines a 13th-century tale, as told by Gonzalo de Berceo and Alfonso X, of a Jewish father who tries to burn his son alive in an oven for having converted to Christianity. It shows how the typological significance of the Virgin Mary's intervention, when she rescues the boy from the oven, is influenced by a legend from the Arabic Infancy Gospel, first in early Latin sources for the miracle, and even more so in medieval Iberian retellings. Finally, it takes into consideration how this anti-Jewish story relates to a 15th-century tale, attributed to Jaume Roig, in which the villain is recast as a Moor and earlier typologies and evangelizing messages have no place, in a retelling that anticipates a more racist notion of identity.
Keywords: Anti-judaism; Arabic Infancy Gospel; Medieval Spain/Iberia; Miracles; Typology